Pengembagan Media Pembelajaran Board Game Go-Metra untuk Kemampuan Berpikir Kreatif Matematis Materi Transformasi Geometri - Tsani, Dyan Falasifa; Saminanto; Saputra, Wahid Rasyid (Circle: Jurnal Pendidikan Matematika, 2021)
Mathematical creative thinking skills need to be developed to help students adapt to a changing world and require them to work flexibly. Besides that, educational games that provide various strategies can help to improve creative thinking skills. Therefore, this study aims to produce learning media in the form of games that can be used to improve mathematical creative thinking skills with the ADDIE development model. Testing of learning media is carried out by testing the validity, practicality, and theoretical effectiveness. The results of this study indicate that the learning media developed are in the very valid category with a final average of 4.43. The practicality and effectiveness of the learning media when viewed theoretically fall into the very practical and very effective category with final averages of 4.55 and 4.82 respectively.